Autophagy governs erythroid differentiation both in vitro and in vivo. Issue 4 (20th April 2016) - Cao, Yan; Cai, Jinyang; Li, Xin; Yuan, Na; Zhang, Suping
Abstract : Objectives : Although the importance of autophagy in determination of cell fate has been much explored in recent years, its definite role in regulating erythroid differentiation remains unclear. Methods : In this study, human erythroleukemic cell line K562 was employed as a cell model for studying erythroid differentiation in vitro . Starvation and rapamycin were used to induce autophagy, whereas Baf-A1 and CRISPR/Cas9/ Atg7 were used to inhibit late and early phase of autophagy, respectively. The mice model of autophagy activation and autophagy deletion were established, and red blood cell counts and flow cytometry were used to analyze erythroid differentiation in vivo . Results : The results showed that the transcriptional levels of α-globin and γ-globin, and the ratio of hemoglobin-positive cells all significantly increased in K562 cells with starvation and rapamycin treatment, which were blocked by autophagy inhibitor, Baf-A1 or Atg7 gene knockout. In the autophagy-enhanced mouse model, the number of mature erythrocytes significantly increased, while in Atg7 -deleted mouse model, erythroid differentiation was severely blocked. Conclusion : It is concluded that autophagy is indispensible in the development, maturation, and homeostasis of erythroid cells both in vitro and in vivo . Our findings support the potential strategy for erythroleukemia treatment and production of erythroblasts in vitro by modulating autophagy.